Dysfunction of the stress response in individuals with persistent post-concussion symptoms: a scoping review protocol. (22nd October 2021) - Farrell, Gerard; Chapple, Cathy; Kennedy, Ewan; Sampath, Kesava; Gisselman, Angela Spontelli; Cook, Chad; Tumilty, Steve
Abstract: Background: 10-15% of individuals who sustain a concussion develop persistent post-concussion symptoms (PPCS). Presently, there is no consensus regarding the pathophysiology of PPCS. Preliminary evidence suggests that individuals with PPCS have either a dysfunctional autonomic nervous system (ANS) or hypothalamic-pituitary-adrenal axis (HPA-axis). The ANS and HPA-axis collectively make up the two arms of the peripheral stress response. In the presence of a stressor, the two arms work interchangeably to return the body back to homeostasis. With concussion as the stressor, it is plausible that the development and maintenance of PPCS are due to a dysfunctional stress response. Only one study has explored the relationship between PPCS and the two arms of the stress response (ANS and HPA-axis) in combination, which presents a clear gap in the literature. Objective: The proposed protocol aims to determine the extent of evidence for dysfunction of the stress response in individuals with PPCS. This review will individually map the literature surrounding quantifiable changes in the (1) ANS and (2) HPA-axis in individuals with PPCS. The review will also highlight any (3) knowledge gaps in this emerging field of research. Methods: A scoping review study design has been chosen to facilitate a thorough literature search on this broad exploratory topic. The scoping review proposed will follow the recommended methodological guidelines. Conclusion: Understanding the potential role of a dysfunctional stress response in those with PPCS will create more effective treatment pathways and reduce the chronicity of this condition.